Marketing Communication Strategy for Potential Clients and Consumers at Giara and Master Wedding Organizer - Putri Maharani Yuniza; Suheri Harahap (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to examine and compare the marketing communication strategies ( Integrated Marketing Communication ) implemented by Giara Wedding Organizer and Master Wedding Organizer towards two different audience entities, namely clients and potential consumers ( leads ) . The fundamental problem in this research is the existence of a gap and fluctuation in conversion from the awareness stage to purchasing action . , where Giara Wedding Organizer as a new business actor does not yet have a clear marketing communication mix, while Master Wedding Organizer already has this communication mix . This research uses a qualitative approach with a comparative case study method . Data collection techniques were carried out through interviews, observations, and documentation with the Owner of Giara Wedding Organizer and Master Wedding Organizer . Data collection focused on five main elements of the integrated marketing communications mix, namely advertising media ( advertising ) , sales promotion​ , public relations​ , face to face selling ( personal selling ) , and direct marketing . The analysis aimed to see how the mix was implemented, both as a retention and relationship maintenance tool for clients , and as a persuasion, education, and conversion tool for potential consumers . Furthermore, the study identified supporting factors (such as effective communication and a solid work team) and inhibiting factors (such as differing expectations and budget constraints) in the implementation of this communication.